Harimau Malaya : biografi Tengku Mahmood Mahyiddeen - Mohd. Zamberi A. Malek (Bangi : Penerbit Universiti Kebangsaan Malaysia, 1999)
Biography of Mahmood Mahyiddeen, 1908-1954, nationalist, educationalist, and politician of Malaysia.
PS-Segera-Pn.Norbaizura-3 naskhah - P.Peng.Sejarah,Politik (SPE)-Ashe Enterprise
Includes bibliographical references (p. [175]-178) and index.
Keywords: Mahmood Mahyiddeen, -- 1908-1954.; Nationalists -- Malaysia -- Biography; Malaysia -- Politics and government